2023
DOI: 10.1039/d2lc01076c
|View full text |Cite
|
Sign up to set email alerts
|

Integrated “lab-on-a-chip” microfluidic systems for isolation, enrichment, and analysis of cancer biomarkers

Abstract: Liquid biopsy has garnered considerable attention as a complementary clinical tool for the early detection, molecular characterization and monitoring of cancer over the past decade. In contrast to traditional solid...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 201 publications
0
8
0
Order By: Relevance
“…Microfluidic devices have been widely used to handle particles (either synthetic or biological) for chemical, biomedical, and environmental applications. Focusing particles into a narrow stream is usually a necessary step in many of these devices such as a flow cytometer and a particle sorter. Both externally imposed (e.g., acoustic, electric, magnetic, etc.) and internally induced (e.g., inertial and elastic lift) forces have been utilized to move particles across streamlines for sheath-free focusing.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic devices have been widely used to handle particles (either synthetic or biological) for chemical, biomedical, and environmental applications. Focusing particles into a narrow stream is usually a necessary step in many of these devices such as a flow cytometer and a particle sorter. Both externally imposed (e.g., acoustic, electric, magnetic, etc.) and internally induced (e.g., inertial and elastic lift) forces have been utilized to move particles across streamlines for sheath-free focusing.…”
Section: Introductionmentioning
confidence: 99%
“…New microfluidic LOC platforms are always under development with the goals of making isolation more sensitive and making in situ analysis even easier. The present trend and desire for the development of "smart" systems that are both highly functional and easy to use, especially for those without a background in POCT, are congruent with this [23]. Furthermore, the initial stride towards individualized healthcare may lie in the development, standardization, and utilization of such cutting-edge technology.…”
Section: Discussionmentioning
confidence: 91%
“…The potential of exosomes as a fluid biopsy for the identification of cancer biomarkers has garnered increasing attention during the past decade. Research like these has shown how critical it is to develop innovative methods for accurately and quickly separating exosomes from bodily fluids with little sample preparation time required [21][22][23][24][25]. Serious problems with purity and more intact performance arise when exosomes are exposed to contaminants and mechanical damage.…”
Section: Discussionmentioning
confidence: 99%
“…Microfluidic technologies, sometimes referred to as "lab-on-a-chip" provide an opportunity to create devices or chips that could compete with classical techniques in biomedical and chemical research. [149][150][151][152] These low-cost devices can process microliters of solution via capillary channels in a high-throughput manner, thus reducing the requirement for samples and reagents. Importantly, all reactions and washing steps are performed in sealed reaction systems, ideal for preventing cross-contamination.…”
Section: Microfluidics and Lab-on-a-chip Technology-integrating Indiv...mentioning
confidence: 99%